1998
DOI: 10.1038/sj.gt.3300564
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the immune response to an adenovirus vector and enhancement of intratumoral transgene expression by low-dose etoposide

Abstract: Adenoviral vectors are commonly used in gene therapyimmunized animals treated with etoposide or cyclophostrials because of their efficiency in gene transfer. However, phamide. Neutralizing antibodies to adenovirus and cytotheir use is limited by cellular and humoral immune toxic T lymphocyte (CTL) lysis of virally transduced cells responses that result in temporary transgene expression were significantly suppressed in mice treated with etopoand reduced efficacy of repeated vector administration. We side at 2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…1,3 Previous studies addressing repeated dosing with rAAV vectors have provided contradicting data. Successful repeated administration after pretreatment of the host with immunosuppressing antibodies, 19 and/or immunemodulating agents 20 or broad immunosuppressing agents, 21 has been reported. Independent of immunosuppressive/modulating regimens, two studies have observed that rAAV may be efficiently Figure 4 Development of NAB (a) and biodistribution (b) in female BALB/c mice after intratracheal and intranasal application of 10 10 and 10 9 AAV-luc (n¼5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Previous studies addressing repeated dosing with rAAV vectors have provided contradicting data. Successful repeated administration after pretreatment of the host with immunosuppressing antibodies, 19 and/or immunemodulating agents 20 or broad immunosuppressing agents, 21 has been reported. Independent of immunosuppressive/modulating regimens, two studies have observed that rAAV may be efficiently Figure 4 Development of NAB (a) and biodistribution (b) in female BALB/c mice after intratracheal and intranasal application of 10 10 and 10 9 AAV-luc (n¼5).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 A number of studies have reported successful repeated administration after pretreatment of the host with immunosuppressing antibodies, 19 and/or immune-modulating agents 20 or broad immunosuppressing agents, such as cyclophosphamide. 21 In contrast to the use of immunosuppressive/modulating regimens, two studies have observed that rAAV may be efficiently administered a second time if the time between administrations is extended beyond approximately 28 weeks and the capsid is derived from AAV5 or AAV9. 8,22 These encouraging results are contradicted by Sumner-Jones et al, 17 where administration of rAAV5 resulted in the production of sustained anti-AAV5 capsid-NAB that substantially lowered lung gene transfer on a second administration and effectively abolished it on a third.…”
Section: Introductionmentioning
confidence: 99%
“…In human tumors, p63 is not frequently mutated like p53, but certain isoforms are occasionally lacked or overexpressed (Crook et al, 2000;Hibi et al, 2000;Nylander et al, 2000;Park et al, 2000;Senoo et al, 2001a). It is known that p53 represses VEGF expression (Bouvet et al, 1998;Fontanini et al, 1998;Mukhopadhyay et al, 1995), which is considered to be a critical regulator for tumor growth. In this study, we have investigated functional roles of p63 on VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor p53 is suggested to have a negative role on VEGF expression (Bouvet et al, 1998;Fontanini et al, 1998;Mukhopadhyay et al, 1995). At the molecular level, it has been shown that p53 inhibits HIF1 activity by targeting the HIF1a subunit for ubiquitination and proteasomal degradation (Ravi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with reports of adenoviral gene transfer in which cellular infiltrates about transfected cells are regularly observed. [12][13]22 The failure of the complex to induce a 'danger' signal in the vicinity of the transfected cells may reduce the host's immune response to the transgene.…”
Section: Discussionmentioning
confidence: 99%